Epidemiological investigation of Senecavirus A infection in pig herds in China from 2018 to 2021 - Li, Chenyu; Gao, Chunliu; Tao, Longfei; Cui, Jin; Zhang, Hui; Zheng, Hui; Wei, Rong; Gu, Shaopeng; Sha, Zhou; Ni, Bo (Frontiers in Veterinary Science, 2024)
Senecaviurs A (SVA) infection, an emerging infectious disease in pig populations, is characterized by vesicular lesions predominantly affecting the mouth, snout, and hooves of infected pigs, similar to the symptoms of Foot and Mouth Disease Virus (FMDV). This disease first spread into China in 2015, causing great panic in the pig breeding industry. To determine the prevalence of SVA in pig herds in China from 2018 to 2021, a total of 4,901 pig tissue samples were collected from 18 provinces, autonomous regions and municipalities (P.A.M.s) for epidemiological investigation, virus isolation and genetic analysis. In 2021, the individual positive rates (IPRs) from the perspective of spatial distribution in East China, South China, Central China, North China, Southwest China, Northwest China, and Northeast China were 0%, 0%, 1.69%, 0.94%, 11.70%, 3.31% and 2.21%, respectively. The herd positive rates (HPRs) were 0%, 0%, 9.52%, 9.09%, 50.00%, 7.69% and 23.08%. From the perspective of temporal distribution, the IPR showed an overall downwards trend from 2018 to 2021, with only a slight increase in 2020. Moreover, the HPR decreased from 36.63% to 10.07%. From the perspective of population distribution in 2021, the IPR (2.62%) and HPR (12.00%) in apparently healthy pig herds (slaughterhouses) were greater than those in non-healthy pig herds (2.10% and 5.13%, respectively), consistent with the results in 2019. To characterize the prevalent strains, 10 SVA strains isolated from positive samples in 2019 were clustered in Clades I and VII;